Invasive mole presenting as acute abdomen- a case report - Peea, AJ (Mediscope, 2017)
Gestational trophoblastic neoplasms include the tumour spectrum of hydatidiform mole (complete and partial), invasive mole, (chorioadenoma destruens), placental site trophoblastic tumour and choriocarcinoma. Here a case is reported as invasive hydatidiform mole presenting as an acute haemoperitoneum. The patient presented with acute abdominal pain and signs of haemoperitoneum. Emergency laparatomy releaved a perforating molar pregnancy, resulting in massive haemoperitoneum. Total hysterectomy was done, 5 units blood were transfused. Serum _HCG levels regress quickly and spontaneously. Mediscope Vol. 4, No. 1: Jan 2017, Page 38-39